Alkyne Insertion Enabled Vinyl to Acyl 1, 5‐Palladium Migration: Rapid Access to Substituted 5‐Membered‐Dihydrobenzofurans and Indolines. (10th March 2023) - Ding, Mingruo; Ou, Pengcheng; Li, Xuening; Yu, Yinghua; Niu, Mengmeng; Yang, Yongjian; Huang, Yewei; Wang, Zhi‐Xiang; Huang, Xueliang
Abstract: "Through space" palladium/hydrogen shift is an efficient strategy to achieve selective functionalization of a specific remote C−H bond. Compared with relatively extensive exploited 1, 4‐palladium migration process, the relevant 1, 5‐Pd/H shift was far less investigated. We herein report a novel 1, 5‐Pd/H shift pattern between a vinyl and an acyl group. Through the pattern, rapid access to 5‐membered‐dihydrobenzofuran and indoline derivatives has been achieved. Further studies have unveiled an unprecedented trifunctionalization (vinylation, alkynylation and amination) of a phenyl ring through 1, 5‐palladium migration relayed decarbonylative Catellani type reaction. A series of mechanistic investigations and DFT calculations have provided insights into the reaction pathway. Notably, it was unveiled that the 1, 5‐palladium migration in our case prefers a stepwise mechanism involving a Pd IV intermediate. Abstract : We herein report a novel 1, 5‐palladium/hydrogen shift pattern between a vinyl and an acyl group, which provides a divergent access to substituted 5‐membered‐dihydrobenzofurans and indolines. Further studies unveiled a novel relayed decarbonylative Catellani‐type reaction. Mechanistic investigations including DFT calculations have shed light on the reaction pathway.